The effect of cartoon on the immediate motor executive function of 4-6 year old children - Sanketh, .; Kommu, Peter Prasanth Kumar; Solomon, Susan; Krishnan, Lalitha; S., Saravanan; K., Ravichandran (International Journal of Contemporary Pediatrics, 2017)
Background: Children’s television viewing has been of concern to parents, educators and health care providers for almost as long as the television itself has been in existence. Objective of present study was to investigate the effect of cartoon viewing on the immediate motor executive function of 4-6 year old children. Methods: 279 children, aged 4-6 year old children were administered the Seguin Form board test to confirm they were all developmentally equal. These children were then randomly assigned to watch a fast paced television cartoon, a slow paced cartoon or colour an image. Following this they were then given 3 tasks to assess motor executive function, including the colour match, 4 two piece puzzle and separating coloured beads. The time taken to complete the task was noted and the data was analyzed. Results: Children who watched the fast-paced cartoon performed slower on the motor executive function tasks than the children in the other two groups. (p<0.001). Conclusions: Even ten minutes of viewing a fast paced television cartoon had immediate negative effects on 4-6 year old children’s motor executive function. Parents should be aware that fast paced cartoon shows could at least temporarily impair young children’s motor executive function.